2013
DOI: 10.1111/joca.12018
|View full text |Cite
|
Sign up to set email alerts
|

Taking Advantage of a Vulnerable Group? Emotional Cues in Ads Targeting Parents

Abstract: Parents of small children regularly face challenges that are new to them, creating uncertainties and stress that complicate their decisionmaking processes. In this vulnerable state, parents may be susceptible to emotional appeals in advertisements in ways that influence their knowledge formation, food choices, and perceptions of self. In this study, we use a combination of content analysis and interviews to examine the use of emotional appeals, particularly guilt and fear, in food ads and how parents respond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Despite a few exceptions (Block, 2005;Brennan & Binney, 2010;Passyn & Sujan, 2006), researchers have paid limited attention to the relationships between several different emotions communicated within the same message. This is surprising since many appeals in practice elicit different emotions and guilt/fear often coexist (Huhmann & Brotherton, 1997;Stanton & Guion, 2013). The elicitationconsumption framework supports the analysis of these relationships and offers new opportunities for researchers wishing to explore how guilt and fear affect consumers' decisions in social marketing campaigns.…”
Section: Applying the Elicitation-consumption Framework To Guilt And mentioning
confidence: 90%
“…Despite a few exceptions (Block, 2005;Brennan & Binney, 2010;Passyn & Sujan, 2006), researchers have paid limited attention to the relationships between several different emotions communicated within the same message. This is surprising since many appeals in practice elicit different emotions and guilt/fear often coexist (Huhmann & Brotherton, 1997;Stanton & Guion, 2013). The elicitationconsumption framework supports the analysis of these relationships and offers new opportunities for researchers wishing to explore how guilt and fear affect consumers' decisions in social marketing campaigns.…”
Section: Applying the Elicitation-consumption Framework To Guilt And mentioning
confidence: 90%
“…The text used in advertisements are considered as a verbal component, it includes all the headlines, taglines, and copy used to narrate the marketing communications. These elements can also evoke positive emotional appeals like excitement and joy, or negative feelings like fear and shame, as observed by Stanton and Guion (2013). Emotional appeals can also be presented through what consumers hear in advertisements (Mogaji & Farinloye, Attitudes towards brands and advertisements: qualitative and thematic analysis of social media data, 2017; Mogaji, Farinloye, & Aririguzoh, Factors shaping attitudes towards UK bank brands: An exploratory analysis of social media data, 2016); this varies from background music, a voice-over, and even the dialogue in the advertisement.…”
Section: Emotional Appeals In Advertisementmentioning
confidence: 93%
“…Consequently, "to be a proper and good mother is to be anxious, to be without anxiety is to lack the motivation to address the risks inherent in having a baby" (Theodorou and Spyrou 2013, p. 82). Stanton and Guion (2013) report that FTMs were more likely to express feelings of guilt and being judged by certain advertising images and messaging related to parenting compared to experienced moms who were more objective. They found that FTMs had more difficulty discerning marketing language from useful information (potentially resulting from a lack of experience or a transitioning self-image as a mother).…”
Section: Vulnerable Mothersmentioning
confidence: 97%